EGFR mutation subtypes and response to immune checkpoint blockade treatment in non-small-cell lung cancer. (14th May 2019) - Hastings, K; Yu, H A; Wei, W; Sanchez-Vega, F; DeVeaux, M; Choi, J; Rizvi, H; Lisberg, A; Truini, A; Lydon, C A; Liu, Z; Henick, B S; et al.
Abstract: Background: Although EGFR mutant tumors exhibit low response rates to immune checkpoint blockade overall, some EGFR mutant tumors do respond to these therapies; however, there is a lack of understanding of the characteristics of EGFR mutant lung tumors responsive to immune checkpoint blockade. Patients and methods: We retrospectively analyzed de-identified clinical and molecular data on 171 cases of EGFR mutant lung tumors treated with immune checkpoint inhibitors from the Yale Cancer Center, Memorial Sloan Kettering Cancer Center, University of California Los Angeles, and Dana Farber Cancer Institute. A separate cohort of 383 EGFR mutant lung cancer cases with sequencing data available from the Yale Cancer Center, Memorial Sloan Kettering Cancer Center, and The Cancer Genome Atlas was compiled to assess the relationship between tumor mutation burden and specific EGFR alterations. Results: Compared with 212 EGFR wild-type lung cancers, outcomes with programmed cell death 1 or programmed death-ligand 1 (PD-(L)1) blockade were worse in patients with lung tumors harboring alterations in exon 19 of EGFR ( EGFR Δ19 ) but similar for EGFR L858R lung tumors. EGFR T790M status and PD-L1 expression did not impact response or survival outcomes to immune checkpoint blockade. PD-L1 expression was similar across EGFR alleles. Lung tumors with EGFR Δ19 alterations harbored a lower tumor mutation burden compared with EGFR L858R lung tumors despite similar smoking history. Conclusions: EGFR mutant tumors have generally low response to immune checkpoint inhibitors, but outcomes vary by allele. Understanding the heterogeneity of EGFR mutant tumors may be informative for establishing the benefits and uses of PD-(L)1 therapies for patients with this disease.